PENGUATAN KEMAMPUAN BERPIKIR LOGIS PADA GURU-GURU PPKn DI MGMP MAGETAN - Oksiana Jatiningsih; Siti Maizul Habibah; Agus Satmoko Adi; Totok Suyanto; Warsono Warsono (Universitas Negeri Surabaya, 2021)
Logical thinking is a way of thinking that leads a person to be able to make correct statements and decisions based on logic and rationale. This skill is indispensable in communicating and writing scientific papers. Based on preliminary observations made, this is one of the obstacles experienced by PPKn teachers in Magetan in scientific writing. Therefore, through this logical thinking exercise, efforts were made to strengthen the logical thinking skills of teachers who are members of the MGMP PPKn Magetan. In accordance with that, the purpose of this service activity is to increase teacher understanding of the rules of logical thinking and increase the ability of teachers to think logically in the context of scientific writing. The activity which was attended by 25 PPKn teachers was carried out at SMA Negeri 1 Magetan, with stages: revealing fallacy in thinking through exercises, discussions about logical thinking fallacies, strengthening logical thinking rules, and logic-based writing exercises. This service activity has been successful in improving the basics of the teacher's ability to think logically. The teacher better understands that in writing, careful thinking logic is needed, the ability to compose simple logical writing also increases, but to be able to write scientifically that can be published, further training and assistance is needed.